The leks of Polistes dominula paper wasps: tiny abdominal spots play a critical role in male attacks toward potential rivals. Issue 4 (4th July 2017) - de Souza, André R.; Lino-Neto, José; Tibbetts, Elizabeth A.; Turillazzi, Stefano; Beani, Laura
Abstract : Leks are characterized by strong male competition and female mate choice. While there is convincing evidence that female choice on leks may be based on male ornaments, little is known about the possibility that the same traits can also mediate conflicts among rivals. Males of Polistes dominula paper wasps have variable yellow abdominal spots. In an earlier experiment in a glass arena, these spots functioned as sexually selected signals: males with elliptical spots were dominant over rivals and preferred by females compared to males with irregularly shaped spots. Whether male spots are sexually selected signals under field conditions is an open question. By conducting a decoy challenge in a natural lek, we observed that lures with manipulated spot shape received more aggression by territorial males when they had regular than irregular spots; these results suggest that males with regular spots were perceived as potentially dangerous rivals. Lekking males could use these condition-dependent ornaments to quickly assess the fighting ability of rivals and to mediate aggressive interactions.